Unification of Financial Management, Corporate Performance, and Business Sustainability of PT Rajalia Mandiri Sejahtera On Jeneponto Regency - Andi Asti Handayani; Tuti Supatminingsih; Sudirman Sudirman (STIE AMKOP, 2026)
This study aims to analyze the implementation of financial management, identify factors affecting the effectiveness of financial management, evaluate its contribution to corporate performance, and formulate financial management strengthening strategies to support business sustainability at PT Rajalia Mandiri Sejahtera in Jeneponto Regency. The study employed a qualitative approach with a case study design through interviews, observations, and documentation. The findings reveal that the company has implemented financial management functions including budgeting, cash flow management, operational cost control, and periodic financial performance evaluation. The main factors influencing the effectiveness of financial management include human resource competence, internal control systems, and the utilization of information technology. More structured financial management practices have contributed to improving operational efficiency, liquidity, and company profitability. The recommended strengthening strategies include financial system digitalization, enhancement of human resource competencies, strengthening internal control systems, and integration of data-based performance monitoring systems to support long-term business sustainability. Keywords: Financial Management; Corporate Performance; Business Sustainability; Digitalization; Internal Control.